Bridging research information systems using web services - Tapulado Rochelle E. (2010)
This study was done to implement web service technology to facilitate data exchange among three independent research information systems, and test if these web services could exchange data between each other. Each of the research information systems provides information on the researches by browsing and searching these researches and viewing the information about the research. Each system was employed with web services to communicate with the other information systems. Two parties are involved in this communication, the service requestor, that calls the service and the service provider, that provides the operations for that service. Employing web services involved creating a Web Service Description Language (WSDL) document for each of the three systems. WDSL is an XML document that contains the description and specifications for the data types returned, the name of the operations used and the location of the web service. While getting data from the local database of one of the systems using web services, data from the two external systems can be requested through request messages and in return the service provider replies with a response message. These request and response messages are transported through XML serialization, the standard protocol for SOAP web services
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: Web services; XML; WSDL; SOAP; Research portal; Research information system